Implementasi Kebijakan Kurikulum Merdeka dan Dampaknya terhadap Kualitas Pembelajaran di Sekolah Menengah Atas - Zainun, Zainun; Arifin, Muhamad (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
The Merdeka Curriculum (Independent Curriculum) emerges as a strategic response to the need for a more adaptive and learner-centered transformation of Indonesia’s national education system. At the senior high school level, this policy requires institutional readiness, competent educators, and well-aligned supporting regulations. This study aims to analyze the implementation, benefits, challenges, and policy directions underlying the adoption of the Merdeka Curriculum in senior high schools. Employing a qualitative descriptive-analytical approach, data were collected from academic literature, official reports issued by the Ministry of Education, Culture, Research, and Technology, as well as findings from relevant previous studies. The analysis explored the interrelation between policy design, classroom implementation, and its impact on the quality of learning in senior high schools. The findings reveal that the implementation of the Merdeka Curriculum is being carried out gradually, depending on the readiness of human resources and school infrastructure. The curriculum offers teachers greater flexibility in designing contextual learning while promoting collaboration among schools, parents, and the community. Nonetheless, several challenges remain, including disparities in school readiness, limited pedagogical and digital competencies among teachers, and the need for continuous evaluation of policy effectiveness. The Merdeka Curriculum has shown positive impacts on post-pandemic learning recovery and the strengthening of students’ Pancasila character values. Its success largely depends on coherent policies, improved teacher competencies, and systemic support from multiple stakeholders. The implication is that the implementation of the Merdeka Curriculum should be accompanied by the continuous capacity building of schools and teachers to ensure a sustainable learning movement that remains relevant to the dynamics of 21st-century education.